Development of power diode numerical modeling for inverse simulation - Yin, Jiaoli. (2008)
In this project a PC program is written to model the characteristics of the power diode under various conditions, including the forward bias, the reverse bias, the turn-on and the turn-off conditions. The results of the simulation of the program are compared with the results from MEDICI that is popular simulation software based on workstation. The comparison shows that the PC program can do accurate or even better simulation for all doping structures and lifetime profiles.